Internal Marketing and Burnout: An Exploratory Analysis in Romanian Health Care Organizations - Iuliana-Raluca GHEORGHE; Victor-Lorin PURCĂREA; Consuela-Mădălina GHEORGHE; Adela-Magdalena CIOBANU; Ovidiu POPA-VELEA (Communications of International Proceedings, 2020)
Burnout is an increasingly prevalent syndrome among physicians, with specific organizational factors contributing to its alleviation. This study aimed to assess the prevalence of burnout, its association with Internal Marketing (IM), and the use of IM practices within Romanian health care organizations. 332 Romanian physicians completed the Maslach Burnout Inventory–GS, the Internal Marketing Questionnaire, and a survey regarding socio-demographic and occupational characteristics. Statistical analyses included χ2 for individual differences, Pearson correlations to measure the relationships between study variables, and hierarchical regressions, for the associations between IM, socio-demographic and occupational factors, and burnout. The prevalence of high-level burnout was 22.6%, with IM accounting for 67% of burnout variance. The IM usage was moderate (48.8%) and often not labeled as such. IM, multiple jobs and specialty were significant predictors of global burnout and cynicism (p
Keywords: Internal Marketing; health care organizations; organizational behavior; Public Health strategies.